Sites of interaction between SecA and the chaperone SecB, two proteins involved in export - Randall, Linda L. (Cold Spring Harbor Laboratory Press, 2004)
SecB, a small tetrameric cytosolic chaperone in Escherichia coli, facilitates the export of precursor poly-peptides by maintaining them in a nonnative conformation and passing them to SecA, which is a peripheral member of the membrane-bound translocation apparatus. It has been proposed by several laboratories that as SecA interacts with various components along the export pathway, it undergoes conformational changes that are crucial to its function. Here we report details of molecular interactions between SecA and SecB, which may serve as conformational switches. One site of interaction involves the final C-terminal 21 amino acids of SecA, which are positively charged and contain zinc. The C terminus of each subunit of the SecA dimer makes contact with the flat β-sheet that is formed by each dimer of the SecB tetramer. Here we demonstrate that a second interaction exists between the extreme C-terminal α-helix of SecB and a site on SecA, as yet undefined but different from the C terminus of SecA. We investigated the energetics of the interactions by titration calorimetry and characterized the hydrodynamic properties of complexes stabilized by both interactions or each interaction singly using sedimentation velocity centrifugation.